Sengers syndrome caused by biallelic TIMM29 variants and RNAi silencing in Drosophila orthologue recapitulates the human phenotype - Adel Shalata; Ann Saada; Mohammed Mahroum; Yarin Hadid; Chaya Furman; Zaher Eldin Shalata; Robert J. Desnick; Avraham Lorber; Asaad Khoury; Adnan Higazi; Avraham Shaag; Varda Barash; et al. (Human Genomics)
Abstract Purpose Sengers-syndrome (S.S) is a genetic disorder characterized by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis. All reported cases were genetically caused by biallelic mutations in the AGK gene. We herein report a pathogenic variant in TIMM29 gene, encoding Tim29 protein, as a novel cause of S.S. Notably, AGK and Tim29 proteins are components of the TIM22 complex, which is responsible for importing carrier proteins into the inner mitochondrial membrane. Method Clinical data of 17 consanguineous patients featuring S.S was obtained. Linkage analysis, and sequencing were used to map and identify the disease-causing gene. Tissues derived from the study participants and a Drosophila melanogaster model were used to evaluate the effects of TIMM29 variant on S.S. Results The patients presented with a severe phenotype of S.S, markedly elevated serum creatine-phosphokinase, combined mitochondrial-respiratory-chain-complexes deficiency, reduced pyruvate-dehydrogenase complex activity, and reduced adenine nucleotide translocator 1 protein. Histopathological studies showed accumulation of abnormal mitochondria. Homozygosity mapping and gene sequencing revealed a biallelic variant in TIMM29 NM_138358.4:c.514T > C NP_612367.1:p.(Trp172Arg). The knockdown of the Drosophila TIMM29 orthologous gene (CG14270) recapitulated the phenotype and pathology observed in the studied cohort. We expand the clinical phenotype of S.S and provide substantial evidence supporting TIMM29 as the second causal gene of a severe type of S.S, designated as S.S- TIMM29. Conclusion The present study uncovers several biochemical differences between the two S.S types, including the hyperCPKemia being almost unique for S.S-TIMM29 cohort, the different frequency of MMRCC and PDHc deficiencies among the two S.S types. We propose to designate the S.S associated with TIMM29 homozygous variant as S.S-TIMM29.